Inhibitory effects of limonin on the proliferation of non-small cell lung cancer cells via targeting S-phase kinase-associated protein 2 - Zhu Jiaxian; Zhang Mengting; Li Shengqing; Liu Yongqiang (生物医学转化)
Objective Aims to investigate the inhibitory effects of limonin on the proliferation of non-small cell lung cancer (NSCLC) cells and its molecular mechanisms. Methods To investigate the inhibitory effects of limonin on NSCLC cell activity, the MTT assay was employed. Then, flow cytometry was used to detect the cell cycle and apoptosis, while colony formation assay assessed the low-density proliferation ability of NSCLC cells. The matrigel 3D pelletization assay was performed to evaluate stem cell properties. Further, Western blotting was used to analyze the underlying molecular mechanisms of limonin inhibiting NSCLC cell proliferation. Cell thermal shift assay (CETSA) was used to demonstrate the binding capability of limonin with target proteins, and molecular docking was employed to predict the interaction sites between limonin and target proteins. Finally, the study utilized small interfering RNA (siRNA) and S-phase kinase-associated protein 2 (Skp2) overexpressing cell lines to validate the molecular mechanisms of limonin inhibiting NSCLC cell proliferation. Results Limonin inhibited NSCLC cell proliferation in a dose-dependent manner by inducing cell cycle G0/G1 phase arrest while significantly attenuating NSCLC stem cell-like properties. Mechanistically, limonin was bound to the Skp2 protein and induced its downregulation, thus promoting the accumulation of its substrate protein p27. Skp2 knockdown by using Skp2-specific siRNA markedly enhanced the inhibitory effects of limonin on NSCLC cell activity. At the same time, Skp2 overexpression attenuated the capability of limonin to inhibit NSCLC cell activity, further validating the underlying molecular mechanisms of limonin inhibiting NSCLC cell proliferation by targeting Skp2. Conclusion Limonin inhibits NSCLC cell proliferation by targeting Skp2 protein to increase the level of the tumor suppressor protein p27, providing crucial theoretical support for the development of limonin as an antitumor drug.